Neural Tube Defects and ZIC4 Hypomethylation in Relation to Polycyclic Aromatic Hydrocarbon Exposure - Huang, Yun; Lin, Shanshan; Wang, Chengrong; Pi, Xin; Jin, Lei; Li, Zhiwen; Wang, Linlin; Ren, Aiguo (Frontiers in Cell and Developmental Biology, 2020)
Background: Epigenetic dysregulation is one of the postulated underlying mechanisms of neural tube defects (NTDs). Polycyclic aromatic hydrocarbons (PAHs), a group of environmental pollutants that are reported as a risk factor of NTDs, may cause decreased genome-wide DNA methylation. With DNA extracted from neural tissues, this study identified gene(s) whose hypomethylation was related to elevated risk for NTDs and examined whether its hypomethylation is related to PAH exposure. Results: Using data profiled by Infinium HumanMethylation450 BeadChip array from 10 NTD cases and 8 controls, ZIC4, CASP8, RAB32, RARA, and TRAF6 were identified to be the top 5 genes in NTD-related hypomethylated gene families. Among all identified genes, ZIC4 had the largest number of differently methylated CpG sites (n = 13) in the promoter and 5'UTR. Significantly decreased methylation in ZIC4 promoter and 5'UTR was verified in an independent cohort of 80 cases and 32 controls (p < 0.001) utilizing the Sequenom EpiTYPER platform. Hypomethylation of ZIC4 was associated with a higher risk of NTDs (adjusted OR = 1.08; 95% CI: 1.03, 1.13) in a logistic regression model. Mean methylation levels in the promoter and 5'UTR region of ZIC4 tended to be inversely associated with levels of high-molecular-weight PAHs in fetal liver among NTD fetuses (β [95% CI]: - 0.045 [-0.091, 0.001], p = 0.054). Six and three CpG sites in ZIC4 promoter and 5'UTR were inversely correlated with antioxidant indicators and protein oxidation markers (ρ: -0.45 to -0.75, p < 0.05) in fetal neural tissues, respectively. In a whole-embryo cultured mouse model, hypomethylation of Zic4 promoter and 5'UTR, and upregulation of Zic4 were observed, coupled with increased NTD rates after BaP exposure. The antioxidant N-acetyl-L-cysteine normalized the changes observed in the BaP exposure group. Conclusions: Hypomethylation of ZIC4 promoter and 5'UTR may increase the risk for NTDs; oxidative stress is likely to play a role in the methylation change of Zic4 in response to PAH exposure in NTD formation.